Inovasi Media Pembelajaran Kaidah Bahasa Arab Melalui Aplikasi Quizlet - Pratama, Raenza Agung; Daroini, Slamet; Sholihah, Mamluatu (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
Learning foreign languages ​​ cannot be separated from learning media, the application of learning media in the learning process is closely related to psychological development and the level of ability of students as learners. Most students of Al-Hamra Islamic Middle School Malang complained about the difficulty of understanding Arabic learning materials due to a lack of understanding of Arabic grammar. In addition, the limited ability of teachers with facilities and time also has an impact on the learning process. This study aims to describe the development of Arabic grammar learning media based on the quizlet application at Al-Hamra Islamic Middle School Malang and its effectiveness. This research using the development approach of the ADDIE development model. Researcher conducted interviews, observations, questionnaires, and tests as data collection techniques. The data analysis technique used the Miles and Huberman method for qualitative data, the Likert scale and SPSS (Paired Sample Test) for quantitative data. The results of the study showed that the media development process in this study went through five stages such as analysis, design, development, implementation, and evaluation. With the Paired Sample Test, obtained the result from implementation of Arabic grammar learning based on the Quizlet application was effective.